The relationship between adverse childhood experiences and educational disadvantage: A critical perspective. Issue 4 (November 2020) - Goodall, Karen; Robertson, Hannah; Schwannauer, Matthias
Abstract : In the last 25 years, converging evidence has supported the view that adverse childhood experiences (ACEs) have long term negative impacts on physical and mental health. More recently, ACEs have been negatively associated with a range of educational measures. As educational attainment is a determining factor in later socioeconomic position, the education system is likely to play a significant role in responding to ACEs. A critical and reflective examination of the available research will be crucial to intervening in evidence-based ways. While the ACEs movement has been instrumental in highlighting the educational impact of inequality in childhood, the ACEs research is often difficult to parse due to a reliance on checklists and a cumulative risk model. At present, the mechanisms that link ACEs to educational outcomes are still under-researched. Continued discussion of the concept of ACEs and the strengths and limitations of the current research is warranted.